Seller Concentration, Barriers to Entry, and Rates of Return in Thirty Industries, 1950-1960 - Mann, H. Michael (The Review of Economics and Statistics, 1966)
CONVENTIONAL price theory predicts that industries in which output is produced by a few dominant firms may, in the long run, earn higher rates of return on the owners' investment than the opportunity cost of the equity capital, commonly called the normal or competitive rate of return. The emphasis on the long run recognizes that actual profit rates differ from normal in the short run for reasons independent of the number of sellers, e.g., changes in demand or cost which raise or lower profits until the reallocation of resources pushes the industry toward long-run equilibrium. The word may indicates that seller concentration is a necessary, but not sufficient, condition. For instance, if the few sellers fail to cooperate with regard to price and output, profits well turn out to be normal. Or, if entry is relatively easy, the oligopolists set a price close to the competitive level in order to discourage potential entrants. A price policy so designed is called pricing, the limit being that price above which entry would be attracted.' Joe Bain has examined the latter possibility by measuring the influence of barriers to entry, classified as very high, substantial, and moderateto-low, on the profit rates of the leading firms in a sample of oligopolistic industries for the periods 1936-1940 and 1947-1951.2 He expected that the price and the monopoly price would probably coincide in the very high barrier class while oligopolists in markets with substantial or moderate barriers might find it profitable to set an entry-forestalling price below the monopoly level, a price which approaches the competitive price as entry barriers decrease. Therefore, profit rates should decline as barriers to entry decrease. Bain found a distinct difference between the average profit rates of those industries in the very high barrier category and those in the other classes. No such clear difference appeared between the substantial and the moderate-to-low barrier classes. He further found . . that seller concentration alone is not an adequate indicator of the probable incidence of extremes of excess profits and monopolistic output restriction. The concurrent influence of the condition of entry should clearly be taken into account.' The purpose of this paper is to present the results of research into the relationship between seller concentration, barriers to entry, and profit rates for 1950 to 1960 to determine whether the pattern Bain found holds for a period of time that was not part of the Great Depression or of rapid postwar inflation. The findings support Bain's results, suggesting that a beginning has been made toward the accumulation of some evidence regarding the influence of two major aspects of market structure on rates of return.